An Asian Integral Ecological Theology: Pope Francis’s Teaching in Dialogue with Asian Religions - Phan, Peter C. (International bulletin of mission research, 2023)
This article presents Pope Francis’s ecological theology, especially as presented in his Laudato Si’ and Querida Amazonia, and places it in dialogue with the ecological thought in Buddhism and Daoism. It begins by placing Pope Francis’s teaching in the environmental context of Asia. It then compares it with the statements on ecology by the Federation of Asian Bishops’ Conferences, especially regarding what Francis terms “the globalization of the technocratic paradigm” and the “excessive anthropocentrism.” The article then relates these two critiques to the Buddhist concept of interdependent origination, especially as presented by the Vietnamese Buddhist Thich Nhat Hanh, and the Daoist concepts of de, dao, wuwei, and ziran. It ends by showing where Pope Francis’s ecological theology could be expanded by addressing the population issue, the theology of the “Cosmic Christ,” and an evolution-based theology of creation. The substance of this article was presented during the twenty-second Louis Luzbetak Lecture on Mission and Culture at Catholic Theological Union, Chicago, on October 18, 2021 (watch the video at https://learn.ctu.edu/2021-luzbetak-lecture). The author is grateful to its organizers for the opportunity to discuss Laudato Si’.